Structural optimization of an external gear pump casing and gears using finite element analysis and response surface methodology - Habi, N.; Bachene, M.; Rebhi, R.; El-Hadj, A. Abdellah; Hayal, Mohammed R.; Ahammad, Sk. Hasane; Elsayed, Ebrahim E.; Juraev, Davron Aslonqulovich (Edelweiss Applied Science and Technology, 2026)
This study presents the structural analysis and optimization of an external hydraulic gear pump with the aim of improving mechanical performance while reducing material usage and overall mass. The work addresses two main aspects: optimization of the pump casing and optimization of the internal gears. The geometric model was constructed in SolidWorks with fully parameterized dimensions to enable an efficient optimization workflow. Finite Element Analysis (FEA) in ANSYS Workbench was used to evaluate stress and deformation under realistic operating conditions. For the pump casing, simulation results were integrated into a Response Surface Methodology (RSM) framework to assess the influence of geometric parameters on structural behavior. The optimized casing achieved a 9.5% weight reduction while ensuring structural integrity, with a maximum deformation of 0.031 mm, a maximum stress of 127 MPa, and a safety factor of 3. The efficiency-to-mass ratio improved from 7.9 to 8.8. In parallel, optimization of the gear pair focused on minimizing stress concentrations and improving stiffness. Using ANSYS simulations combined with RSM, the optimized gear design reduced von Mises stress from 239.4 MPa to 224 MPa, reflecting better load distribution and enhanced durability. Overall, the results demonstrate the effectiveness of integrating finite element simulation with response surface optimization to achieve structural and performance improvements in hydraulic gear pumps.